Mecanismo de cianossililação de aldeídos catalisada pela MOF MIL-101(Cr) - Aline de Oliveira (2015)
The Metal-Organic Framework (MOF) MIL-101(Cr) has been reported as a good catalyst for cyanosilylation reactions. This process constitutes an important step in the preparation of compounds like -aminoalcohols, -hydroxyacids, -hydroxyketons and -aminoacids, which are very useful in the synthesis of pharmaceuticals and agrochemicals. MIL-101(Cr) is a highly porous solid, with large pores and, therefore, it can be used as heterogeneous catalyst in processes which involve bulky substances, such as the molecules of biological interest. Understanding at the molecular level the performance of this MOF as a catalyst in cyanosilylation of aldehydes is extremely important, because it would allow the identification of the characteristics of this material that make the catalysis possible. Thus, the obtained information could help the design of new MOFs that are more efficient or, different ways to optimize the catalytic activity of MIL-101(Cr). In this work, the catalytic properties of this material are investigated for the cyanosilylation reaction of aldehydes through DFT calculations. Whence, mechanisms of aldehydes conversion in their respective trimethylsilylated cyanohydrins were performed, through the addition of trimethylsilyl cyanide. Five catalyzed mechanisms were studied using models of metallic clusters to describe the catalytic site of MIL-101(Cr) and three non-catalyzed mechanisms were also analyzed, in order to be compared to the catalyzed processes. The results indicate that both, the catalyzed and the non-catalyzed mechanism, occur through concerted processes, in which there is formation of a transition state with a five-membered cycle. Furthermore, the catalytic performance of MIL-101(Cr) probably occurs due to the presence of Lewis acidic sites, which come from coordinatively unsaturated chromium(III) ions in regions of crystal defects, located in the material structure, or in its surface. Thereby, one way of enhancing the catalytic properties of MIL-101(Cr) would be through their preparation by synthetic routes that lead to defects in this solid structure.